Literatur Review: Analisis Pengaruh Pepohonan Sawit Terhadap Suhu Disekitarnya Menggunakan Internet Of Things (IoT) Sensor Dh22 - Eka Ariyani Safitri; Eva Gusmira (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Palm oil is an industrial/agricultural crop that is processed into vegetable oil, industrial oil and fuel raw materials. In developing oil palm farming, the problem faced by entrepreneurs and farmers involved is the procurement of planting materials. Of the oil palm business activities, especially in planting and watering plants, many still use manual seeding methods. Starting from oil palm nurseries with manual irrigation. This means that irrigation is carried out in the morning and evening via a hose connection. Day, for watering the seeds and lighting the planted seeds, direct sunlight and oil light intensity are still used. Temperature is the degree of hot or cold measured on a certain scale and can be measured with a thermometer. Temperature is usually expressed in degrees Celsius (°C). Internet of Things (IoT) is the concept that certain objects can send and receive data via a WiFi network, so that this process does not require human-to-human or human-to-computer interaction. The DHT 22 sensor is a digital sensor that can measure temperature from -40°C to 125°C and humidity from 0% to 100% of the surrounding air. This sensor is very easy to use in conjunction with Arduino. It has a high level of stability and very accurate calibration features. The temperature and humidity sensor used in making this tool is DHT22.